Improved process performance in new product development of optical communications manufacturing by the integration of DFSS and ANP. (1st January 2012) - Lin, Wen-Tsann; Wang, Shen-Tsu; Hwang, Chen-Hsang; Li, Meng-Hua; Cheng, Yu-Hsiu
In the trend of increasingly fierce global competition of optical communications industries, design for Six Sigma (DFSS) provides a systematic management approach using tools, training, and measurement methods to achieve products, services, and process designs that meet customer expectations. Taking transnational optical communications original equipment manufacturer (OEM) as the research objects, this study applied IDEF0, analytical network process (ANP), performance matrix analysis, and system simulation to propose a management model, which integrates DFSS with the development processes of new products for improvement and reengineering. The proposed research analysis model can reduce new product development process time by 30.24%. The findings of this research can serve as reference for the introduction of new product development process performance improvements.